Si9+ Ion-Irradiation Induced Modification of Structural and Magnetic Properties of Zn-Nanoferrite. (1st May 2022) - Parmar, C.; Verma, R.; Modak, S. S.; Mazaleyrat, F.; Kane, S. N.
Abstract : We report synthesis of ZnFe2 O4 by sol gel auto-combustion technique, and study the effect of 120 MeV 28 Si 9+ ion irradiation (dose: 1 × 10 12 −1 × 10 14 ions cm −2 ) on structural, magnetic properties, correlation between them, probed by X-ray diffraction "XRD, " scanning electron microscopy-energy dispersive X-ray analysis "SEM–EDX, " magnetic measurements. Formation of single-phase spinel nanoferrite (grain diameter: 15.93–16.92 nm), is confirmed by XRD. EDX-SEM confirms formation of desired phase, non-homogeneous particle size dispersal. Results show that with increasing irradiation dose, lattice parameter decreases;reduction of Fe 3+ ions on B-site, with concurrent increase on A-site, while Zn 2+ ions remain more populated on A-site than on B-site. Irradiation shows decrease of oxygen positional parameter, and strain, increase of inversion-degree, modification of A–O–B, A–O–A, B–O–B super-exchange interaction, reduction of dead-layer thickness, resulting in reduction of coercivity, saturation magnetization. Linear dependence of coercivity on grain diameter suggests the studied samples lie in overlap-region between multiple-domains or single-domain.